Benefits of and Best Practices for International Experiences for College Students: A Synthesis of the Literature - Katy E. Lane; Theresa P. Murphrey (Journal of International Agricultural and Extension Education, 2020)
Implementation of international experiences for students has increased. Anecdotal evidence suggests that these experiences enhance the quality of students upon graduation. However, a synthesis of literature related to the benefits of international experiences was lacking. We rooted the study’s conceptual framework in the concept of high-impact activities/experiences and related inputs, processes, and outcomes with a focus on the benefits of student participation in an international experience. Our purpose was to establish a benchmark documenting research conducted related to the benefits of an international experience and to identify research gaps. The rigorous literature review process identified 108 articles published across 55 unique publications for inclusion. Documentation of benefits was grouped into four categories: personal growth, international knowledge, cultural awareness, and additional skills. Further, the literature revealed a litany of reasons that students chose not to participate and a wide range of guidance for program planning. We conclude that research has documented specific benefits of students’ participation in international experiences; however, many of these studies are based on data collected immediately following the experience rather than longitudinal data. Our research synthesis provides a summary of benefits and program strategies for utilization by researchers in planning future research and by practitioners in planning future international experiences.
Keywords: study abroad; international experience; benefit; cultural understanding; benchmark